IMPROVING THE EDUCATIONAL PROCESS BASED ON THE USE OF INFORMATION LEARNING MANAGEMENT SYSTEMS - Aleksandra B. Kriger (Открытое образование (Москва), 2016)
The paper considers with the development of effective educational process, using leaning management system. The analysis of the results of the use Blackboard Learning System for the organization of educational activities to the university students. Built process models of learning (ideal and real) on the basis of their proposals on the improvement of the educational process.